The Concept of Peace in the Al-Qur'an Pespective - Mukhtar Nuhung; Abdul Rahim (International Journal on Advanced Science, Education, and Religion, 2018)
Conflicts, disputes, and acts of terrorism have become a daily scene, both in the nature of individuals, communities, tribes, religions, and even between nations. Al-Quran as a way of live always leads Muslims to live safely and peace away from the conflict. Thus, the main problem arising from this research is how the concept of peace in the Qur'an. This discussion aims to know how the nature of peace, how the form of peace, and how the goals and benefits of peace according to the Qur'an. It is intended to provide a comprehensive understanding of the concept of peace that exists in the Quran. The research is a library research which is qualitative. Data and information obtained through several literatures were analyzed using content analysis. The approach used was the "science of interpretation" with the method maud} u> i> / thematic. In interpreting the data, some interpretation techniques were used: textual interpretation, linguistic, socio-historical, systemic, and logical interpretation, The results show that there were verses in the Qur'an that explains about peace meaning human being free from conflict and war, free from civil instability and free from disturbance of riot, violence and so on. The concept of the Quran on peace is the order of peace (is} la> h}), and the command to reconcile conflicting people or groups. The object of peace is humanity as a whole. Peace aims to stop conflict between human beings. Both reconcile directly between the conflict, as well as peace through the mediator. The benefits of peace are; ensuring the stability of security and economy, the creation of a sense of peace of mind in marriage, community and nation, The implications of the study emphasize that the study of verses on the concept of peace in the Qur'an includes the needs of human life in national and state society, so it needs to be developed primarily in the current era of globalization, because the analysis of the verses of peace can provide motivation, inspiration and innovative spirit to elaborate the values of togetherness in living life in various aspects which in turn mankind can improve the quality of life in qur'ani. This study is not only limited to knowing and understanding but by applying it in everyday life by minimizing the occurrence of conflict, violence, discrimination, injustice so as to realize safe and peaceful people who love togetherness in knitting life in this world that is safe, happy and prosperous .